Cerebrovascular ischemic changes associated with fetal posterior cerebral artery- descriptive retrospective study with magnetic resonance imaging and angiography of brain - Venkatraman Indiran; Prabakaran Maduraimuthu (Al Ameen Medical College, 2016)
Objectives: Circle of Willis, the main collateral pathway for cerebral circulation, is complete in only a portion of the population. There are many variations in the Circle of Willis. Fetal posterior cerebral artery, which is defined as posterior cerebral artery arising from internal carotid artery, is a common variant of the Circle of Willis. Though association between the fetal posterior cerebral artery and ischemia have been studied, no specific study has been conducted in the Indian population. We aim to identify the incidence of small and large vessel strokes in patients with fetal posterior cerebral artery using Magnetic Resonance Imaging (MRI) and Magnetic Resonance Angiography (MRA) of brain in the Indian population. Materials and methods: We retrospectively reviewed MR angiographies of the brain performed in our institution, in order to assess the posterior cerebral circulation and its association with small ischemic changes and large vessel strokes. Results: 92 of the 140 patients (65%) with fetal posterior cerebral artery (PCA) had small vessel ischemic changes. 72 patients (51.4%) had large vessel infarcts in any of the vascular territories. 35% of the patients included in this study showed infarcts in the middle cerebral artery (MCA) territory and 15 % showed infarcts in the PCA territory. Conclusion: Higher incidence of MCA infarcts in our study probably suggests that PCA cannot aid in collateral formation cases of reduced flow across the internal carotid artery and that fetal PCA could be an important risk factor in cerebrovascular ischemic diseases.